ANALISIS KEBUTUHAN PRIMARY AIR PADA KILN BURNER UNTUK MEMPRODUKSI KLINKER - Panjaitan, Jabosar Ronggur Hamonangan; Tursida, Faiza; Rahmadini, Gustia; Putra, Rahman Etika ((JITEK)Jurnal Ilmiah Teknosains, 2024)
Clinker is the main ingredient in cement production which was produced by calcination process in a kiln with a burner. In this research, air requirements for the combustion process in burner to produce clinker were investigated. Based on the results, it was found that the air requirement for fuel combustion process was 127,403.849 (Nm3/hour). The combustion air requirement if 8% primary air used was 10,192.3 (Nm3/hour) and for 10% primary air used was 12,740.38 (Nm3/hour). The operational primary air flow (10.6%) was close to the theoretical primary air flow (10%), which operational primary air flow was 13,504.8 (Nm3/hour) and theoretical primary air flow (10%) was 12,740.38 (Nm3/hour).